METHOD AND ERROR ESTIMATION OFDECISIONS IN DETERMININGAND OF OBJECTSI N SPACE - Мироненко, Ольга (SWorldJournal, 2022)
The methodsof estimation of errors of solutions of navigational data processing tools (so-called one-step methods, on the examples of Metoda Eiler, method a Runge-Kutta, which can be used, for global navigational satellite systems (GSS) determination of